Assessing employees' commitment and the relationships with perceived organizational support in contract-out facility management services - Azizan, Mat Rashib (2014)
This quantitative research paper aims to determine the relationship between perceived organizational support (POS) with Organizational Commitment (OC) among the Facility Management (FM) employees from three (3) government premises in Kuala Lumpur. The FM contractor‘s company enters an FM contract with the government to deliver the contract-out FM services in the three (3) government premises. The FM employees are those who belong to the FM contractor‘s company, but stationed fulltime in the three (3) government premises to deliver the contract-out FM services. Therefore, the relationships between POS with OC as well as with the OC‘s components were identified in this kind of environment. Respondents for this study comprised of 68 FM employees from the three (3) premises. The three (3) premises are simply labeled as Premise A, Premise B and Premise C to keep the anonymity of the FM contractor companies. Data were analyzed using Statistical Package For Social Sciences (SPSS) Version 16 software. Tests conducted were Pearson Correlation analysis and Simple Linear Regression analysis. The correlation analysis results suggest that POS have significant positive linear relationship with OC, as well as with each OC‘s components which is affective commitment (AC), normative commitment (NC) and continuance commitment (CC), with moderate strength of association. Subsequently, the first simple linear regression result concluded that POS is positively significant with OC with 47.2% of the variance in OC is explained by the variance in POS. Further, another three separate simple linear regression were done to determine the relationship between POS with AC, NC, and CC, respectively. Similarly, the results confirmed that POS positively significant with and could influence AC, NC, and CC. Recommendations were also being suggested to the management of the FM contractor‘s company to enhance the level of FM employees‘ OC since their POS were at moderate level. These can be done by formulating programs that could make the FM employees perceive their company highly support them in term of valuing their contributions and cares about their well-being